2006
DOI: 10.18388/abp.2006_3314
|View full text |Cite
|
Sign up to set email alerts
|

Melanin synthesis in microorganisms--biotechnological and medical aspects.

Abstract: Melanins form a diverse group of pigments synthesized in living organisms in the course of hydroxylation and polymerization of organic compounds. Melanin production is observed in all large taxa from both Pro- and Eukaryota. The basic functions of melanins are still a matter of controversy and speculation, even though their adaptative importance has been proved. Melanogenesis has probably evolved parallel in various groups of free living organisms to provide protection from environmental stress conditions, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
197
0
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(224 citation statements)
references
References 138 publications
5
197
0
11
Order By: Relevance
“…indirectly upregulate melanin production, thus explaining why sometimes melanin hyperpigmentation occurs in association with inflammatory oral mucosal conditions. 4,12,13 Melanocytes in the basal cell layer of the oral epithelium are more or less uniformly distributed among the basal keratinocytes, 3 It has been reported that physiological oral melanin pigmentation might develop during the first two decades of life, and occurs more frequently in darker people. 1,3,4,9,10,16 The difference in oral pigmentation among different racial/ethnic groups and between individuals of the same racial/ethnic group is attributed to an increased production | 3 of 6 of melanin, rather than to an increase in the number of oral melanocytes.…”
Section: Resultsmentioning
confidence: 99%
“…indirectly upregulate melanin production, thus explaining why sometimes melanin hyperpigmentation occurs in association with inflammatory oral mucosal conditions. 4,12,13 Melanocytes in the basal cell layer of the oral epithelium are more or less uniformly distributed among the basal keratinocytes, 3 It has been reported that physiological oral melanin pigmentation might develop during the first two decades of life, and occurs more frequently in darker people. 1,3,4,9,10,16 The difference in oral pigmentation among different racial/ethnic groups and between individuals of the same racial/ethnic group is attributed to an increased production | 3 of 6 of melanin, rather than to an increase in the number of oral melanocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Melanins form a heterogeneous group of polymeric dark pigments produced by different living organisms including humans, animals, plants, and microorganisms. 1 Despite their widespread distribution among living cells, little is still known on their exact structure. 2 So far, most of melanins appear to be phenolic or indolic-based polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Other metabolic roles of melanin such as electron acceptor or role in nitrogen fixation in bacteria have been documented. [14] It has been suggested that melanin may serve as a structure strengthening agent by cross-linking of proteins. [11] Raman spectroscopy was previously demonstrated as an excellent tool to characterize microbiological pigments.…”
Section: Introductionmentioning
confidence: 99%